(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article provides detailed information about the engineering and communication systems necessary for modern buildings and structures - cold water, hot water, heat supply, irrigation, fire water supply and sewage (wastewater disposal) networks. Each one of the system main tasks , structural parts and schematic structures illuminated . In the article engineering approaches , inter-systems mutual dependency and effective exploitation for important technician to the requirements separately attention focused on . Material project engineers , technicians experts and construction in the field students for useful source is considered .